Panoramic radiography in the diagnosis of carotid artery atheromas and the associated risk factors - Henriques, João César Guimarães [UNESP]; Kreich, Eliane Maria [UNESP]; Baldani, Márcia Helena; Luciano, Mariely; de Melo Castilho, Julio Cezar [UNESP]; de Moraes, Luiz Cesar [UNESP] (Bentham Science Publishers, 2011)
Atherosclerosis is a serious chronic disease, responsible for thousands of deaths worldwide and is characterized by thickening and loss of elasticity of the arterial walls, associated with the presence of atheromatous plaques. Various risk factors act directly on predisposition to the disease, among which the following are pointed out: diabetes mellitus, arterial hypertension and inadequate diet and eating habits. More recent researches have elucidated new risk factors acting in the development of this disease, such as, for example: periodontitis, chronic renal disease and menopause. The panoramic radiograph, commonly used in dental practice, makes it possible to see calcified atherosclerotic plaques that are eventually deposited in the carotid arteries. The aim of this review article was to emphasize the dentist's important role in the detection of carotid artery atheromas in panoramic radiographs and the immediate referral of patients affected by these calcifications to doctors. In addition, the study intended to guide the dentist, especially the dental radiologist, with regard to differential diagnosis, which should be made taking into consideration particularly the triticeal cartilage when it is calcified. © Henriques et al.
Keywords: Atherosclerosis; Carotid artery diseases; Panoramic radiography; Risk factors